2004
DOI: 10.1073/pnas.0405502101
|View full text |Cite
|
Sign up to set email alerts
|

Anticorrelated motions as a driving force in enzyme catalysis: The dehydrogenase reaction

Abstract: A present issue concerns the occurrence of rate-promoting vibrations, which assist in lowering barrier height in enzyme catalysis (1-5). A related issue addressed here is the question of whether certain thermal Brownian motions of an enzymesubstrate complex (E⅐S) participate in lowering the energy barrier of activation (6) by creating the most reactive groundstate conformations [near-attack conformers (NACs) (7)]. One such possibility is that ground-state conformations, which lead directly to the lowest energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 33 publications
3
58
0
Order By: Relevance
“…Molecular dynamics and normal mode analyses suggest that motions of domains (related to the global conformational change) could “push” the substrates together. 13,86 Equilibrium, vibrational motions might also be sufficient, however, as temperature factors of 10 Å 2 (observed in these structures, albeit at 100 K) could correspond to motions of 0.35 Å, leading to a decrease in the donor-acceptor distance from 3.4 to 2.7 Å. However, a recent, empirically-parameterized model suggests that the “tunneling ready state” could have a donor acceptor distance of 3.2 Å.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular dynamics and normal mode analyses suggest that motions of domains (related to the global conformational change) could “push” the substrates together. 13,86 Equilibrium, vibrational motions might also be sufficient, however, as temperature factors of 10 Å 2 (observed in these structures, albeit at 100 K) could correspond to motions of 0.35 Å, leading to a decrease in the donor-acceptor distance from 3.4 to 2.7 Å. However, a recent, empirically-parameterized model suggests that the “tunneling ready state” could have a donor acceptor distance of 3.2 Å.…”
Section: Resultsmentioning
confidence: 99%
“…Such motion allows substrate diffusion to the active site of the enzyme. Previous studies of enzyme MD by Bruice and coworkers (24) have also identified anticorrelated motions of the active sites as signatures of enzymatic activity. Thus, correlated motions between monomers arise on the nanosecond time scale and are, remarkably, disrupted in the mutant dimers.…”
Section: Resultsmentioning
confidence: 99%
“…95 In subsequent molecular dynamics calculations, residues were ranked as either correlated (moving together) or anticorrelated (moving in opposite directions), with the anticorrelated motions within the cofactor and substrate binding domains proposed to contribute to the reactive conformations leading to catalysis. 96 Schwartz and co-workers have developed a very interesting algorithm for identifying promoting modes in proteins. 97 Using computer modeling with HLADH, they “scale” various active site residues with regard to the likelihood that their motions will be linked to the hydrogen transfer step.…”
Section: Alcohol Dehydrogenasesmentioning
confidence: 99%